Hepatitis B virus X increases immune cell recruitment by induction of chemokine SDF‐1. Issue 5 (23rd January 2014) - Cho, Hyun Kook; Kim, So Young; Seong, Je Kyung; Cheong, JaeHun
Abstract : Hepatitis B virus X protein is a major factor in the HBV‐induced disease developments. Stromal cell‐derived factor‐1 is a small cytokine that is strongly chemotactic for lymphocytes. We explored the role of HBx on recruitment of HBV‐induced virus‐nonspecific immune cells into liver. Immune cell recruitment and SDF‐1 expression level significantly increased in livers of HBx‐transgenic mice and X‐box binding protein‐1 significantly increased SDF‐1 gene expression. Finally, we confirmed that immune cell recruitment into liver tissues of HBx‐TG mice was diminished by a chemokine receptor antagonist. Therefore, HBx increases ER stress‐dependent SDF‐1 expression and induces HBV‐induced immune cell recruitment into liver. Abstract : Immune cell recruitment is increased in HBx‐expressing mice liver. Expression of chemokine SDF‐1 is increased in HBx‐expressing cells and mice. HBx‐induced SDF‐1 expression is mediated by ER stress. ER stress regulator XBP1 increases SDF‐1 expression. Inhibition of SDF‐1‐CXCR4 signaling reduces immune cell recruitment into livers.